Assessment of cellular immunity by CD4+ and CD8+ lymphocyte counts in 2–12-year-old children with iron-deficiency anemia - Pratiksha Khalale; Bharat Umakant Patil; Pravinkumar Ghongade; Anupama Gupta (Saudi Journal for Health Sciences, 2023)
Background: Iron-deficiency anemia (IDA) in children and infants can have long-term adverse consequences on neurodevelopment and behavior, which can be irrevocable in some cases and detrimental to the immune system. Aim: The aim of this study was to investigate the role of IDA and its effects on immunity in CD8 and CD4 lymphocytes. Settings and Designs: This was a prospective study. Materials and Methods: A total of 40 pediatric cases (2–12 years) were first time diagnosed as IDA based on complete blood count (CBC) parameters, peripheral blood smear, and serum ferritin levels. Flow cytometric immune assays were used to determine the number of CD4+ and CD8+ lymphocytes and the ratio of CD4+/CD8+. Statistical Analysis: Pearson's correlation coefficient and Students' unpaired t-test were used. Results: The difference between the case and control groups in hemoglobin (Hb), red blood cell (RBC) indices, red cell distribution width, RBC count, and serum ferritin is highly significant. A significant linear positive association between CD3+ and CD4+ cell counts and serum ferritin and a significant linear positive correlation between CD4+ cell counts and Hb were observed. However, there was a nonsignificant linear positive association of both parameters, hemoglobin (Hb) and mean corpuscular volume (MCV) with CD3+ cell count, CD4+ cell count, and CD4+/CD8+ cell ratio. Conclusion: Iron deficiency does not affect total white blood cell count or differential leukocyte count on routine CBC, but it can alter cellular immunity (CD3+ cell count, CD4+ cell count, and CD4+/CD8+ cell ratio).